Pengaruh Tarif Jasa, Lokasi dan Kualitas Jasa terhadap Loyalitas Pelanggan pada Beauty House Shanda Lahat - Kasinem Kasinem; Mujari Mujari; Hestin Hestin; Iskandar Malian (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study uses causal associative research with a quantitative approach. The sample used in this study was 80 people using a random sampling technique, namely accidental sampling. The results of this study indicate that service rates (X1) have a significant effect on customer loyalty (Y) as evidenced by the t-value of 7.167 > the t-table value of 1.991, so the first hypothesis is proven. The results of the t-test also show that there is a significant influence of location (X2) on customer loyalty (Y) with a t count of 3,908 > t-table value of 1,991, so the second hypothesis is proven. The results of the t-test also show that there is a significant effect of service quality (X3) on customer loyalty (Y) with a t count of 8.881 > t-table value of 1.991, so the third hypothesis is proven. The results of the f test show that service rates (X1), location (X2), and service quality (X3) have a significant effect on customer loyalty (Y) with a calculated f value of 130.309 > f table value of 3.11 so that the fourth hypothesis is proven. The results of the coefficient of determination test can be seen as the value of the coefficient of determination or R Square of 0.772 or equal to 77.2%. This figure means that the Service Rate (X1), Location (X2), and Service Quality (X3) variables have an influential contribution to the Customer Loyalty variable (Y) of 77.2%, while the remaining 22.8% is influenced by other variables. This study did not examine promotion, studio atmosphere, and so on